Tailoring amphiphilic polymeric coating with durable antifogging performance - Gong, Xiaodan; Yu, Haojie; Wang, Li; Hu, Jian; Wang, Luming; Li, Chengjiang (Progress in organic coatings, 2023)
Foggy surfaces can damage the optical performance of devices and even cause adverse consequences like safety concerns in some cases. Various antifogging coatings have been proposed to relieve this trouble. Nevertheless, most coatings suffer from temporary fog-repellency features due to hygroscopic swelling behavior and detachable interface. Herein, we reported an antifogging coating with persistent fogging prevention via the introduction of the amphiphilic polymer and interfacial layer. With the aid of benzophenone (BP) groups, both bulk crosslinking and interfacial bonding were achieved to prevent relatively macroscopic motions of coating from the substrate under extreme conditions. In virtue of the minor swelling and interfacial adhesion, the coating could preserve the fog-free behavior after 50-cycle antifogging tests and even aging for 90 days under harsh conditions. Notably, both in vitro (pig larynx) and vivo (living rabbit) outcomes indicated excellent fog-repellency of the polymer-coated endoscope. [Display omitted] •The antifogging amphiphilic coating was reported.•The photoreactive CH insertion of bulk crosslinking and interfacial bonding was achieved to prevent coating detachment.•Persistent fogging prevention was presented due to the minor swelling and strong interfacial adhesion.•The coating showed potential application on endoscopes for clear fog-free vision.